(untitled) (Social Science Review, 2025)
This article aims to understand the state policies and the specific role played by the Bangladesh National Museum in preserving and safeguarding ethnic cultures in Bangladesh. Three specific objectives were pursued: the description of the provisions outlined in different laws, acts, and policies that are designed to safeguard ethnic cultures, the examination of the diverse ethnic objects’ collections stored in the museum; and the analysis of the role played by the museum in the collection, exhibition, and preservation of objects pertaining to ethnic groups. The anthropological understanding has been used to comprehend ethnic minorities, policy, and the role of the museum. In-depth interviews, KII, and policy document analysis have been used to collect data. The study argues that state policies mostly prioritize infrastructure development programmes, mainstreaming efforts, and the assimilation of ethnic communities rather than establishing specific and contextually appropriate strategies and actions for the preservation of ethnic traditions and customs. Similar to state policy, the museum has collected artefacts from 14 ethnic groups of the country. Most of the collected objects are from Tripura, Garo Chakma, and Santals groups, with six categories of cultural aspects, e.g., ornament, textile, musical instrument, arms, armour and metal. The museum’s identification of some artefacts belonging to ethnic groups is hindered by the improper collecting procedure. Only 2.7% of total artefacts are ethnic objects, which is insufficient to represent all ethnic cultures. The state policy lacks specificity for preserving ethnic cultures, leading to distorted practices by the museum in dealing with ethnic groups, compromising objectivity and universality in museum practices due to inherent politics in policy-making. Social Science Review, Vol. 41(1), June 2024, Page 215-236.